ANALISIS BIAYA DAN PENDAPATAN USAHA PEDAGANG SAYURAN DI PASAR TAMIN KOTA BANDAR LAMPUNG - Romidah Astuti; Wan Abbas Zakaria; Teguh Endaryanto (Lampung University, 2018)
This study aims to analyze the cost structure and the income level of vegetable traders in Tamin Market Bandar Lampung City. This research is conducted in purposively chosen Tamin Market with the consideration that Tamin Market is a center of vegetable trade and the main market in Bandar Lampung City. The data were collected in March 2017 and respondents were 15 vegetable traders who are willing to be interviewed, consisting of five stall traders, five los traders, and five street traders. Data are analyzed descriptively using qualitative and quantitative of cost and income analysis. The result showed that the traders' business cost structure consists of fixed cost and variable cost. The propotion of variable cost is higher than the fixed cost, which is 99 percent of total cost. Variable costs include plastic cost, vegetable purchase, transport, labor, and information. And fixed costs include rent cost, electricity and market facility fees. The average income of stall traders is higher than the loser traders and the street traders. The average income of stall traders is Rp817,055.00 per day, los traders is Rp737,604.00 per day, and street traders is Rp183,455.00 per day.Key words: cost structure, the level of income, vegetable traders